Recursos didácticos digitales: medios innovadores para el trabajo colaborativo en línea - Quirós Meneses, Elionay (2009)
The purpose of this paper is to present the origin, characteristics and rules of the Blogs, Wikis, Chats, Forums, and the Cmap Tools, that one must take into account when working with them as digital resources. In addition, the main contribution offered, is an explanation of possible didactic uses that these resources offer as a dynamic strategic proposal for collaborative e-learning.